Fabrication and Characterization of GO-Fe3O4/PSF Membrane with Phase Inversion Method - Vivia Maulida Alfianti; Munasir Munasir (JPSE (Journal of Physical Science and Engineering), 2021)
Polysulfones are hydrophobic which can reduce membrane permeability. Permeability can be increased through the application of hydrophilic materials such as GO-Fe3O4 to the polysulfone membrane so that the membrane is hydrophilic. The riset purpose to determine the effect of the percentage weight of different material compositions on the hydrophilicity properties of the polysulfone membrane. Membrane fabrication is carried out using the phase inversion method where the polymer solution is molded in a place and immersed in a coagulation bath containing non-solvent. This solvent exchange causes the polymer to form a solid matrix and become a membrane. The results showed that GO particles were successfully doped with Fe3O4 material shown by XRD analysis at a peak of 35.61˚ with a magnetite phase, while FTIR analysis showed that there was an absorption band characteristic of Fe-O streching vibrations. The results of the contact angle test on the GO-Fe3O4/PSF membrane 0.75 wt per cent were around 73.17˚ which showed the smallest hydrophobic value and the membrane surface morphology had an average pore size of 333.61 nm so that the addition of GO-Fe3O4 composites could increase membrane hydrophilicity.DOI: 10.17977/um024v6i22021p055